Gambaran Peran Orang Tua Terhadap Personal Hygine Anak Selama Hospitalisasi - Friska Fajar Khusnul Ambar Sari; Siti Arifah (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Poor personal hygiene in children can cause health problems. Parents play a big role in children's development, playing a role in educating, being role models for children, giving advice, and getting children used to maintaining personal hygiene. Objective: The aim of this research is to determine the role of parents in personal hygiene for children during hospitalization. Method: This research uses descriptive analytics; the sampling technique uses accidental sampling of 22 parents. The instrument used is a questionnaire. Study Results: The research results show that the role of parents in their child's personal hygiene during hospitalization is quite good. Conclusions and Suggestions: Based on the research results, nurses, as educators, can help provide health education to parents about the importance of maintaining children's personal hygiene during the treatment period to increase parents' role in children's personal hygiene.